Initiation fo Ontology, Epistemology, and Axiology in Higher Education Management in The Era Of The Industrial Revolution 4.0 - Walef, Sri Mures; Bestri, Rafikah; Rifma, Rifma; Syahril, Syahril; Jasrial, Jasrial (KOLOKIUM Jurnal Pendidikan Luar Sekolah, 2023)
This research discusses ontology, epistemology and axiology in higher education education management in the era of the industrial revolution 4.0. Descriptive qualitative research methods and literature studies were used in this research. The descriptive method is a problem solving procedure that is investigated by describing the condition of the research subject/object. Through this approach, it is hoped that we will be able to provide deeper, more comprehensive answers, not just surface and theoretical proofs, in accordance with the research objectives to be achieved. The discussion starts from the understanding of ontology, the relationship between ontology and education and the role of ontology in education management, understanding epistemology, the role of epistemology in education management in the era of the industrial revolution 4.0. Next, understanding axiology, the role of axiology in educational management in the era of industrial revolution 4.0. Conclusions, ontology, epistemology and axiology in higher education education management in the era of industrial revolution 4.0, we form a solid philosophical foundation for achieving a relevant and competitive educational vision.